Astroglial cells regulate the developmental timeline of human neurons differentiated from induced pluripotent stem cells - Tang, Xin (2013)
Neurons derived from human induced-pluripotent stem cells (hiPSCs) have been used to model a variety of neurological disorders. Different protocols have been used to differentiate hiPSCs into neurons, but their functional maturation process has varied greatly among different studies. Here, we demonstrate that laminin, a commonly used substrate for iPSC cultures, was inefficient to promote fully functional maturation of hiPSC-derived neurons. In contrast, astroglial substrate greatly accelerated neurodevelopmental processes of hiPSC-derived neurons. We have monitored the neural differentiation and maturation process for up to two months after plating hiPSC-derived neuroprogenitor cells (hNPCs) on laminin or astrocytes. We found that one week after plating hNPCs, there were 21-fold more newly differentiated neurons on astrocytes than on laminin. Two weeks after plating hNPCs, there were 12-fold more dendritic branches in neurons cultured on astrocytes than on laminin. Six weeks after plating hNPCs, the Na(+) and K(+) currents, as well as glutamate and GABA receptor currents, were 3-fold larger in neurons cultured on astrocytes than on laminin. And two months after plating hNPCs, the spontaneous synaptic events were 8-fold more in neurons cultured on astrocytes than on laminin. These results highlight a critical role of astrocytes in promoting neural differentiation and functional maturation of human neurons derived from hiPSCs. Moreover, our data presents a thorough developmental timeline of hiPSC-derived neurons in culture, providing important benchmarks for future studies on disease modeling and drug screening.